What subtypes are driving the association between hypertensive disorders of pregnancy and dementia? Findings from an 80‐year retrospective cohort study. (20th December 2022) - Schliep, Karen Cecilia; Shaaban, C. Elizabeth; Baradaran, Hediyeh; Fraser, Alison; Meeks, Huong; Varner, Michael
Abstract: Background: We recently found that women with, versus without, a history of HDP had a higher hazard of all‐cause dementia, vascular dementia (VaD), and other/unspecified dementia, but not Alzheimer's disease (AD). Here, we assess associations of HDP subtypes with later life dementias. Methods: We performed a retrospective cohort study among women with at least 1 singleton pregnancy (1939–2019) in Utah. Classification of HDP was done via birth certificates (text string, 1939–1977; ICD9 codes, 1978–1988; and check boxes with additional text, 1989–2013) with death certificates and inpatient records used for validation. Classification of dementia was assessed using ICD 9/10 codes via death, inpatient, and Medicare records. HDP exposed women (n=19, 989) were one‐to‐two matched with unexposed women (n=39, 679) by 5‐year age groups, year of childbirth, and parity at the time of pregnancy (Figure 1 ). Cox regression models were used to estimate adjusted Hazard Ratios (aHR) and 95% CI for HDP subtypes with all‐cause and specific dementias. Results: HDP pregnancies were comprised of preeclampsia/eclampsia (65.9%) and gestational hypertension (33.5%). The remaining HDP cases were due to HELLP syndrome (0.6%), which we did not evaluate here due to small case count. Incidence of dementia over follow‐up (1979–2019) was 4.1%; of these, 70% were other/unspecified, 24% were AD, and 6% were VaD. Women with a history of preeclampsia/eclampsia, compared to unexposed, had a 1.38 higher hazard of all‐cause dementia, while women with gestational hypertension had a 1.36 higher hazard (Table 1 ). Breaking down by dementia subtypes, women with a history of preeclampsia/eclampsia had a 1.51 higher hazard of other/unspecified dementia, while women with gestational hypertension had a 1.31 higher hazard. The strength of association of gestational hypertension with VaD was 2.75, nearly double that for preeclampsia/eclampsia, which was 1.58. HDP subtypes were not associated with AD. Conclusion: Our results are in line with the largest study to date conducted in Denmark that found preeclampsia to be most strongly associated with VaD compared to other dementia subtypes. Our results further suggest that risk of VaD may be just as high for women with a history of gestational hypertension as for preeclampsia.